2020
DOI: 10.1016/j.energy.2020.118737
|View full text |Cite
|
Sign up to set email alerts
|

Economic disruptions in long-term energy scenarios – Implications for designing energy policy

Abstract: The main drivers of transformation processes of electricity markets stem from climate policies and changing economic environments. In order to analyse the respective developments, modelling approaches regularly rely on multiple structural and parametric simplifications. For example, discontinuities in economic development (recessions and booms) are frequently disregarded. Distorting effects that are caused by such simplifications tend to scale up with an extension of the time horizon of the analysis and can si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Similarly, Koppelaar et al [10] found that electricity system models are able to provide scenario-based insights for some policy purposes, but not for others, and especially not for the exploration of problem solutions and political or societal paradigm shifts. At the same time, Govorukha et al [50] stress that decision-makers should be better informed about the underlying simplifications applied in modelling: for example, it must be clearly communicated what macro-economic factors are and are not considered in the scenario analysis. All in all, there is plenty of room for modelling improvements to better serve policymaking [11], which requires a better understanding of needs by diverse stakeholder groups.…”
Section: Background: User Needs and Energy Systems Modellingmentioning
confidence: 99%
“…Similarly, Koppelaar et al [10] found that electricity system models are able to provide scenario-based insights for some policy purposes, but not for others, and especially not for the exploration of problem solutions and political or societal paradigm shifts. At the same time, Govorukha et al [50] stress that decision-makers should be better informed about the underlying simplifications applied in modelling: for example, it must be clearly communicated what macro-economic factors are and are not considered in the scenario analysis. All in all, there is plenty of room for modelling improvements to better serve policymaking [11], which requires a better understanding of needs by diverse stakeholder groups.…”
Section: Background: User Needs and Energy Systems Modellingmentioning
confidence: 99%
“…To stay abreast, even long-term scenarios 30 years into the future, like the World Energy Outlook (WEO), are outdated so quickly that they require substantial revision every year. Similar to forecasts, energy scenarios struggle to incorporate exogenous shocks affecting demand or fuel prices [29,20]. In addition, scenarios often neglect major changes and assume an overly conservative continuation of present trends.…”
Section: Coordinating Actorsmentioning
confidence: 99%